Answer:
a = 5 1/3
Step-by-step explanation:
a+b+b = 24
a + 2b = 24
b-a =4
a = b - 4
b - 4 + 2b = 24
3b = 24 + 4
b =28/3
substitute this in a = b - 4
a = 28/3 - 4
a = 28/3 - 12/3
a = 16/3
a = 5 1/3
Answer:
(a) H0:μ1=μ2; Ha:μ1≠μ2, which is a two-tailed test.
Step-by-step explanation:
We formulate the
H0: μ1=μ2; null hypothesis that the two means are equal and alternate hypothesis that the two mean are not equal.
Ha:μ1≠μ2 Two tailed test
Test statistic used is
t= x1`-x2` / s√n as the variances are equal and sample size is same
T value for 9 degrees of freedom for two tailed test at α = 0.05 is 2.26
P- value for t test for 9 degrees of freedom is 0.125 from the table.
Hence only a is correct .
X= -2 or X= 3 either one works.
Answer
-15
Step-by-step explanation:
-13 +24=11
11-46=-35
-35+20=-15
Answer:
the third selection is corret
Step-by-step explanation:
Ax + by + c = 0, k = - a/b.
so The slope of the first line =
,
the slope of the second line =
;
So these two lines are parallel and they don't intersect